Da UNITINS à UFT: modelos e práticas gestoriais na educação superior do estado do Tocantins no limiar do século XXI - Souza, Raquel Aparecida (2007)
This study is inserts in the Line of Politics and Management of the Education of Post- Graduation Course in Education of the Federal University of Uberlândia and takes a central point the field of politics of superior education. More specifically, sought to identify, to analyze and to understand which had been the models and managerial practice present into process of creation and implantation of the Federal University of Tocantins (UFT) and its relation with the University of the Tocantins (Unitins) and its restructure toward the educational politics developing for superior education in the 90 s of century XX. An analysis was developed looked to point out this process in a wide context in which occurred changes in the work world and the process and performance of State, at side of the Brazilian public executive. The study evidenced that, even though the elements considered for the reforms present in the management of university, still is common the presence of patrimonial relations, charismatic and, overall, bureaucratic, developed in the side of controlling management. In relation the methodological aspect, this study has investigative character and works in a perspective of qualitative approach to believe that the conduction of research make possible the construction more global and articulated vision of the investigated object, as well as its interrelation with the social, cultural, economic and politics aspects. After an analyze of socio-historic conditionings that lies in the development of superior education in Brazil, focused the study about creation process and implantation of UFT, searching to apprehend elements about the problematic of research, by means of the collection of data, using, as instruments the half-structuralized interview, the application of online questionnaire and the document analysis. It was evident that, the UFT was created in a context of transformations in the field of superior education, context that the proposal for model of implantation controlling management was emphasize with an necessity, otherwise, that has still predominated elements of a patrimonial management, charismatic and bureaucratic, that has confused in the organizations of the academic activities this institution.